2007
DOI: 10.1038/sj.emboj.7601936
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of FIR upon FUSE DNA binding suggests a mechanism of c-myc inhibition

Abstract: c-myc is essential for cell homeostasis and growth but lethal if improperly regulated. Transcription of this oncogene is governed by the counterbalancing forces of two proteins on TFIIH—the FUSE binding protein (FBP) and the FBP-interacting repressor (FIR). FBP and FIR recognize single-stranded DNA upstream of the P1 promoter, known as FUSE, and influence transcription by oppositely regulating TFIIH at the promoter site. Size exclusion chromatography coupled with light scattering reveals that an FIR dimer bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
71
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 57 publications
12
71
1
Order By: Relevance
“…60 On the other hand, in FBP-Interacting Repressor (FIR) protein, the a-helix face of RRM1 packs onto the b-sheet face of RRM2, creating a stable interface. 61,62 Examples of Trp-mediated homodimerization in other RRM domains have been previously reported, as in the Nup35 protein. 63 In contrast, the RRM modules of the splicing factor Pub60 form a dimeric interface driven by electrostatic interactions involving a flexible loop.…”
Section: Discussionmentioning
confidence: 72%
“…60 On the other hand, in FBP-Interacting Repressor (FIR) protein, the a-helix face of RRM1 packs onto the b-sheet face of RRM2, creating a stable interface. 61,62 Examples of Trp-mediated homodimerization in other RRM domains have been previously reported, as in the Nup35 protein. 63 In contrast, the RRM modules of the splicing factor Pub60 form a dimeric interface driven by electrostatic interactions involving a flexible loop.…”
Section: Discussionmentioning
confidence: 72%
“…4e6 As transcription intensifies, the melted DNA bubble at FUSE expands upstream, allowing the recruitment of FIR via DNA-protein interactions and protein-protein interaction between a shallow groove in FIR RNA recognition motif 2 and the most NH 2 terminal a-helix of FBP ( Figure 10, A and B). 22,23,54,55 FIR then restores TFIIH helicase activity to basal levels, depressing transcription. 7 Falling levels of supercoiling combined with Figure 10 Scheme for FBP operating as a molecular cruise control to help set MYC levels and to constrain fluctuations around the set point.…”
Section: Discussionmentioning
confidence: 99%
“…A and B, 1: MYC transcription is initiated by a conventional transcription factor(s) represented by symbols. FIR's recruitment and dimerization with a second monomer evict FBP 54 and down-regulate MYC ( Figure 10, A and B). Note that the FBP/FIR/FUSE system depends on the action of other transcription factors to trigger MYC transcription and to generate dynamic supercoiling ( Figure 10, A and B).…”
Section: Discussionmentioning
confidence: 99%
“…FIR-FBP-FUSE ternary complexes contact more DNA than FBP-FUSE, but less than FIR-FUSE. Crichlow et al (16) found that FIR binds to a short FUSE oligonucleotide as a dimer, and propose a model where FIR first binds to FBP-FUSE and then evicts FBP by looping or spooling of the DNA. The extended contacts seen with FIR-alone, but not by FBPϩFIR, is compatible with such a structural reorganization.…”
Section: Discussionmentioning
confidence: 99%
“…It is also not known whether FIR binding to the FBP-DNA complex changes FBP's interactions with ssDNA as has been hypothesized (16).…”
mentioning
confidence: 99%